Museum Artifacts as Linguistic Archives: Exploring Linguistic Insights from Timurid Artifacts - Dilafruz Kurbanova; Zukhra Dosmetova; Usmon Karabaev; Eshmamat Khaitov; Noila Nabieva; Gulkhayo Abdullaeva (Jurnal Arbitrer, 2025)
This paper explores museum artifacts from the Timurid period as invaluable linguistic archives, moving beyond traditional historical and artistic interpretations to unveil hidden narratives about past societies. It argues that the linguistic data embedded in inscriptions, manuscripts, coins, and architectural texts offer profound insights into language use, communication practices, and cultural nuances of the Timurid Empire. This paper demonstrates, based on detailed linguistic analysis of a selection of artifacts, that they served as an active repository that both conveyed political power, religious beliefs, kinship systems, and social life. For instance, Persian inscriptions on jugs and ewers underscore artistic expression and imperial authority, while Arabic inscriptions on finger-ring seals and coins highlight religious piety and political legitimacy, blending Mongol traditions with Islamic values. Manuscripts and paintings further illustrate Persian as the dominant literary language and the mechanisms of intellectual and cultural exchange. The article also highlights some issues that can be challenging for linguists when collecting data from museum artefacts, such as text fragmentation and language opacity, particularly in a multilingual environment. To overcome these challenges, this review also proposes methodological approaches, including comparative linguistics, digital epigraphy, and contextual study, to address these challenges. With the robust technology and multidimensional approach, some challenges can be overcome and valuable resources can be provided for further linguistic analysis. This cross-disciplinary initiative transforms objects as vibrant forms of knowing through which one can access a fuller account of the workings of language as an intellectual technology in building and shaping lived experience, values, and power relations in Timurid society, providing productive insights into the ways in which language acts upon culture to advance or undermine social cohesion.